Placenta Accreta and Total Placenta Previa in the 19th Week of Pregnancy - Findeklee, S.; Costa, S. D. (Geburtshilfe und Frauenheilkunde, 2015)
Placentation disorders are the result of impaired embedding of the placenta in the endometrium. The prevalence of these disorders is estimated to be around 0.3 %. A history of previous prior uterine surgery (especially cesarean section and curettage) is the most common risk factor. Impaired placentation is differentiated into deep placental attachment; marginal, partial and total placenta previa; and placenta accreta, increta and percreta. Treatment depends on the severity of presentation and ranges from expectant management to emergency hysterectomy. In most cases, preterm termination of pregnancy is necessary. We report here on the case of a 39-year-old woman with placenta accreta and total placenta previa who underwent hysterectomy in the 19th week of pregnancy.
Keywords: placenta previa; placenta accreta; pregnancy